FEATURES OF INTERACTION IN THE COMPANIES IN СONDITIONS OF DIGITALIZATION DEVELOPMENT - I. Groshev (Publishing House of the State University of Management, 2019)
Digitalization in the modern world has an impact on all spheres of life. Interactions within the company are also changing. For the company to remain flexible, a special approach to workflows and communications is required. Digital tools allow build interaction in the company at a such level, when the maximum circle of people is involved in decision-making in direct contact with customers. The latter are full partners of the company. Hierarchical organizations are being replaced by self-governing systems and new concepts of organizational behavior.